”As you’ve never heard him before!” Jimi Hendrixin musiikin tuotteistaminen 1971–2018 - Rami Mähkä (Suomen musiikkitieteellinen seura, 2022)
Discusses productization and marketing of Jimi Hendrix's music in the decades following his death.